Taxonomic revision of Panicum sect. Hiantes (Poaceae: Panicoideae: Paniceae) - Zuloaga, Fernando Omar (Phytotaxa, 2025)
A worldwide revision of Panicum sect. Hiantes is presented. Considering morphological characters, 36 species and four varieties are recognized. New synonyms are proposed in P. massaiense (P. kasumense and zambesiense), P. ruspolii (P. nubicum), and P. pooides (P. graniflorum). Lectotypes are designated for 27 names. Full synonymies, descriptions, distribution and habitat information, citation of representative specimens and a key to the species of sect. Hiantes are provided. 32 species are illustrated.